(untitled) (Research, Society and Development, 2020)
This report had like goal to show a qualitative exploratory analysis of the role and the typology of experimentation in teaching through annals of the congress of the annual meeting of the Brazilian Chemical Society between 2011 and 2019. The theoretical and methodologic references of the analysis to characterize experiments in teaching were based on the observation of Araújo & Abib and Oliveira. The present research showed that most of the experiments applied in the classroom are of a demonstrative and / or verifying nature, and only 6% of the analyzed works were classified as investigative with a focus on meaningful learning, by applying the experiment as an active methodology, making the student active and central subject in the teaching-learning process. Thus, the such observations suggest, as conclusion, an urgent need to foster good training for teachers able to develop efficient experiments via active methodologies.